2013
DOI: 10.1021/ml4003925
|View full text |Cite
|
Sign up to set email alerts
|

Differential Induction of Cytoplasmic Vacuolization and Methuosis by Novel 2-Indolyl-Substituted Pyridinylpropenones

Abstract: Because many cancers harbor mutations that confer resistance to apoptosis, there is a need for therapeutic agents that can trigger alternative forms of cell death. Methuosis is a novel form of non-apoptotic cell death characterized by accumulation of vacuoles derived from macropinosomes and endosomes. Previous studies identified an indole-based chalcone, 3-(5-methoxy-2-methylindol-3-yl)-1-(4-pyridinyl)-2-propen-1-one (MOMIPP), that induces methuosis in human cancer cells. Herein, we describe the synthesis of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
73
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(81 citation statements)
references
References 18 publications
(42 reference statements)
7
73
0
Order By: Relevance
“…Accumulation of vacuoles ultimately displaces the cytoplasm and the cell membrane loses integrity and ruptures. While dysfunctional vesicular trafficking and accumulation of vacuoles appear to contribute to cell death, there is evidence that additional metabolic or cellular insults are required for execution of the methuosis cell death program [8,10,11]. …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accumulation of vacuoles ultimately displaces the cytoplasm and the cell membrane loses integrity and ruptures. While dysfunctional vesicular trafficking and accumulation of vacuoles appear to contribute to cell death, there is evidence that additional metabolic or cellular insults are required for execution of the methuosis cell death program [8,10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…An initial search for compounds reported to induce cellular vacuolization led us to an indolyl-pyridinyl-propenone (IPP, also referred to as indole-derived chalcone) as a potential lead [13]. Associated structure-activity relationship (SAR) studies revealed that the optimized scaffold for induction of methuosis consists of a 2,5-disubstituted indole and a pyridine in the para -configuration, bridged by an α,β-unsaturated ketone [11,14,15]. Our previously reported IPP compounds, and their modes of biological activity, are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] The nonapoptotic cell death pathway described in those papers "appears similar if not identical to what is described by the Karolinska team, " noted Roth.…”
mentioning
confidence: 69%
“…Similar improvements in activity have been reported due to inclusion of a 5-methoxy group on an indole scaffold elsewhere. [68][69][70] The same group has recently published a paper on the synthesis and activity of a series of MOMIPP analogues, [71] which shows that increasing the size of the aliphatic substituent at the 2-position does not reduce vacuolisation but does reduce the cytotoxicity of the compounds. Work on this form of cell death via the use of indoles is still ongoing by this group.…”
Section: Methuosis Initiatorsmentioning
confidence: 99%